Economic analysis of a hybrid energy storage system based on liquid air and compressed air - Pimm, Andrew James; Garvey, Seamus D.; Kantharaj, Bharath (Elsevier, 2015)
A hybrid energy storage system is defined here as one which comprises two series-connected energy stores (using different storage technologies), only one of which is connected to the grid. Such a plant can take advantage of certain characteristics of different storage technologies, and the example considered in this paper is a liquid air energy storage (LAES) plant with some compressed air energy storage (CAES) capacity, taking advantage of the low storage cost for LAES and relatively high efficiency for CAES. An algorithm is presented which can be used to find the maximum possible profits that may be obtained from a hybrid plant through electricity price arbitrage, and it is shown that a hybrid compressed air–liquid air plant with 2.5:1 ratio of charge time to discharge time profiting purely through arbitrage gives higher profit per unit CapEx than the equivalent pure CAES and pure LAES plant if charge time is longer than 36 h. A realistic control strategy is also presented which can be used if the plant operator has a certain amount of knowledge of future electricity prices. It is shown that, for a given foresight period, the performance of this strategy increases with the plant's round-trip efficiency.